The endocrine response to training - French, D. N. (Strength and conditioning for sports performance, 2016)
Physical training for sports performance, fitness, or health-related benefits represents a potent stimulus that initiates a myriad of systemic changes and physiological adaptations throughout the body. These changes include a cascade of neural, hormonal, metabolic and genetic responses in which the endocrine system plays a central regulatory role [68]. By modulating systemic responses to exercise, the endocrine system is intimately involved with the acute and/or chronic physiological adaptations highly sought after during strength training and physical conditioning.